The mental motivation among graduate students - Dr. Huda Salman Marzouk (Journal of College of Education, 2025)
The current research aims to identify: 1- Mental motivation among graduate students at the University of Wasit. To achieve the objectives of the research, the researcher adopted the scale (Kahil, 2015), which was built according to the theory of (Ginacarlo and Vacchione, 1996), for graduate students. The mental motivation scale consists of (30) items, and the sample of the current research consisted of (400) male and female students from Postgraduate students from both scientific and humanities specializations for the morning study. The research sample was chosen by a random stratified method. After applying the scale to the research sample and processing the data statistically using the SPSS statistical package, the research reached the following results: 1- Postgraduate students have mental motivation. In light of the results of the current research, the research came out with a number of recommendations and proposals.